Belief and Recall of Nicotine as Therapeutic for COVID-19 May Undermine E-Cigarette Quitting Behavior. (December 2022) - Silver, Nathan; Kierstead, Elexis; Tran, Bianca; Sparrock, Lindsey; Vallone, Donna; Schillo, Barbara
We examine the proposition that misinformation about the therapeutic potential of nicotine to prevent or treat COVID-19 may lead to relapse among attempted e-cigarette quitters. A sample of N = 507 e-cigarette ever-users who reported at least one quit attempt in the past year were surveyed in June of 2021 for recall and belief in several claims about COVID-19 and nicotine. Participants who recalled and believed at least one misinformation claim were significantly more likely to have relapsed than those who did not recall or believe such claims. These differences remained robust to regression analysis adding demographic covariates and accounting for continuous measurement of recall and belief. Misinformation about e-cigarette use is reaching young adult e-cigarette users who are trying to quit. The implications of these findings merit further research to characterize potential barriers to successful e-cigarette cessation.